Designing Business Process Improvement that Concentrates on IT Utilization at LPPM UPN “Veteran” Jawa Timur - Mohamad Irwan Afandi; Eka Dyar Wahyuni (Future Science, 2020)
To enhance operational efficiency, several organizations have pursued business process re-engineering initiatives. Inevitably, this initiative involves the modernization and modification of existing information systems to support business processes. UPN